Recent progress of polyamide thin film nanocomposite membranes for water applications - Khoo, Ying Siew; Lau, Woei Jye; Liang, Yong Yeow; Ahmad Fauzi, Ismail (Elsevier, 2020)
Thin film composite (TFC) membranes have been used for industrial processes for several decades without having major problems, but membrane scientists were still making continuous effort over the years to further improve the current membrane performance, aiming to overcome the permeability/selectivity trade-off effect and resistances against fouling, chlorine, and microbial attack. In this chapter, the recent progress of new generation composite membrane-thin film nanocomposite (TFN) membrane incorporated with nanomaterials was reviewed for various aqueous media-based separation processes including reverse osmosis, nanofiltration, and forward osmosis. The key findings of the TFN membrane research were highlighted and further compared with the conventional TFC membranes. Furthermore, the technical challenges of TFN membranes for industrial implementation are also highlighted and discussed.